A review of open source software solutions for developing water resources web applications. (May 2015) - Swain, Nathan R.; Latu, Kilisimasi; Christensen, Scott D.; Jones, Norman L.; Nelson, E. James; Ames, Daniel P.; Williams, Gustavious P.
Abstract: Water resources web applications or "web apps" are growing in popularity as a means to overcome many of the challenges associated with hydrologic simulations in decision-making. Water resources web apps fall outside of the capabilities of standard web development software, because of their spatial data components. These spatial data needs can be addressed using a combination of existing free and open source software (FOSS) for geographic information systems (FOSS4G) and FOSS for web development. However, the abundance of FOSS projects that are available can be overwhelming to new developers. In an effort to understand the web of FOSS features and capabilities, we reviewed many of the state-of-the-art FOSS software projects in the context of those that have been used to develop water resources web apps published in the peer-reviewed literature in the last decade (2004–2014). Highlights: Free and open source software can be used to address the needs of water resources web applications. The large number of open source projects can be overwhelming to novice developers. We present a review of the free and open source GIS and web development software. Software reviewed includes those projects used to develop 45 water resources and earth science web applications. The review highlights 11 FOSS4G software projects and 9 FOSS projects for web development.